PERENCANAAN EMBEDDED WALL TIPE SHEETPILE KANTILEVER SEBAGAI PENAHAN TANAH TIMBUNAN DENGAN METODE ANALISIS KESEIMBANGAN BATAS (STUDI KASUS PROYEK XYZ) - Muhammad Alhan (Jurnal Vokasi Teknik Sipil, 2025)
Soil is an important aspect of construction where a building or other construction is built. Therefore, it is very important to maintain soil stability. One effort to stabilize the soil is with reinforcement such as an Embedded Wall. This research aims to determine the dimensions and depth of Sheet Pile erection that are suitable for the XYZ project. This research uses the limit equilibrium analysis method and processing soil data from the correlation of N-SPT results from the XYZ project. This method emphasizes the balance of active and passive earth pressure in the Cantilever Sheet Pile Type Embedded Wall. This plan resulted in a penetration depth of 8.55 meters. The maximum moment obtained from planning is 488.961 kN.m/m. With these results it was also found that Sheet Pile W-600 Class A from Wika Beton could be used in this project.